Don’t panic: An intron-centric guide to alternative splicing - Petrillo, Ezequiel (2023)
This review is an attempt to establish concepts of splicing and alternative splicing giving proper relevance to introns, the key actors in this mechanism. It might also work as a guide for those who found their favorite gene undergoes alternative splicing and could benefit from gaining a theoretical framework to understand the possible impacts of this process. This is not a thorough review of all the work in the field, but rather a critical review of some of the most relevant work done to understand the underlying mechanisms of splicing and the key questions that remain unanswered such as: What is the physiological relevance of alternative splicing? What are the functions of the different outcomes? To what extent do different alternative splicing types contribute to the proteome? Intron retention is the most frequent alternative splicing event in plants and, although scientifically neglected, it is also common in animals. This is a heterogeneous type of alternative splicing that includes different subtypes with features that have distinctive consequences in the resulting transcripts. Remarkably, intron retention can be a dead end for a transcript, but it could also be a stable intermediate whose processing is resumed upon a particular signal or change in the cell status. New sequencing technologies combined with the study of intron lariats in different conditions might help to answer key questions and could help us to understand the actual relevance of introns in gene expression regulation.